2012
DOI: 10.1128/jvi.00505-12
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Transcription Factor Early Growth Response 1 Reduces Herpes Simplex Virus 1-Induced Corneal Disease in Mice

Abstract: bHerpes simplex virus 1 replication initiates angiogenesis and inflammation in the cornea. This can result in herpetic stromal keratitis (HSK), which is a leading cause of infection-induced corneal blindness. Host cellular factors mediate the progression of HSK, but little is known about these cellular factors and their mechanisms of action. We show here that the expression of the cellular transcription factor early growth response 1 (Egr-1) in HSV-1-infected mouse corneas was enhanced. Enhanced Egr-1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…This observation proposed a connection between neuronal stress and HSV reactivation from latency, suggesting that activation of the Egr-2 from the same stress/stimuli responses may result in LAT suppression and thus play a role in reactivation by abolishing latency. Additional and current studies indicated that during acute infection HSV-1 can directly induce Egr-1 and enhance viral gene expression and replication [2,13,21]. All these results supported the roles of EGR proteins in suppressing latency and promote lytic infection.…”
Section: Discussionsupporting
confidence: 53%
“…This observation proposed a connection between neuronal stress and HSV reactivation from latency, suggesting that activation of the Egr-2 from the same stress/stimuli responses may result in LAT suppression and thus play a role in reactivation by abolishing latency. Additional and current studies indicated that during acute infection HSV-1 can directly induce Egr-1 and enhance viral gene expression and replication [2,13,21]. All these results supported the roles of EGR proteins in suppressing latency and promote lytic infection.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, C57BL/6J mice were infected with 1 ϫ 10 5 PFU of strain McKrae or mock infected on the right eye without scarifying the cornea. RE-infected mouse eyes were examined weekly after infection to monitor corneal opacity and angiogenesis as described in our previous report (35). The corneal opacity was graded on a scale of 0 to 5 as follows: 0, normal cornea; 1, mild corneal haze; 2, moderate corneal opacity or scarring; 3, severe corneal opacity, iris visible; 4, opaque cornea, iris invisible; and 5, necrotizing cornea with vascularization.…”
Section: Methodsmentioning
confidence: 99%
“…Male ICR mice were infected with 1 ϫ 10 5 PFU/eye of 294.1, treated with TCP on the cornea immediately before infection and by intraperitoneal injection 1 day before infection to day 10 p.i., and monitored for body weight and survival. Female C57BL/6N mice were infected with 5 ϫ 10 5 PFU/eye of RE, treated with TCP on the cornea immediately before infection and by intraperitoneal injection 1 day before infection to day 9 p.i., and monitored for corneal opacity and angiogenesis as described in our previous reports (37,40). The corneal opacity was graded on a scale of 0 to 5 as follows: 0, normal cornea; 1, mild corneal haze; 2, moderate corneal opacity or scarring; 3, severe corneal opacity, iris visible; 4, opaque cornea, iris invisible; and 5, necrotizing cornea with vascularization.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…We tested the effect of TCP treatment on reducing the severity of HSV-1-induced stromal keratitis. C57BL/6N mice were corneally infected with wild-type HSV-1 strain RE, which can induce stromal keratitis to result in corneal blindness in mice (37,40). Infected mice were treated with saline or TCP on the cornea immediately before infection and by intraperitoneal injection from 1 day before infection to day 9 p.i.…”
Section: Tcp Treatment Reduces the Titers Of Wild-type And Thymidine mentioning
confidence: 99%